Makna Syukur dalam Tafsir Al-Maragi (Kajian Atas Q.S Luqman Ayat 12, 14, Dan 31) - Khasanah, Uswatun (ojs.unsiq.ac.id, 2022)
Many of the contents of the Qur'an that are taught in Islam include the command to be grateful. That gratitude is God's commandment to all humans for all His blessings bestowed for the provision of worship, therefore gratitude is not as simple as imagined and practiced by society. In writing this thesis the author uses several qualitative research methods, to obtain data, namely by library research, the primary data source the author uses Tafsir al-Maragi and the secondary data source the author uses data related to This study is collected through library research or literature review, books related to the theme. Meanwhile, in collecting data with the interpretation method of tahlili interpretation and to analyze the existing data, the writer uses a descriptive-analytical method. The results showed that the meaning of gratitude in the tafsir al-Maragi (study of QS Luqman) can find out the meaning of the verse that contains the word gratitude, namely QS Luqman [31]: 12 has the meaning of the command of gratitude to Allah Swt, QS Luqman [31]: 14 contains the meaning of gratitude to Allah SWT and gratitude to parents, QS Luqman [31]: 31 contains the meaning of gratitude for favors related to the signs of His power. And can show the contextualization of the meaning of the verses of gratitude in the discussion in Indonesia, so that it is hoped to be able to apply it in life.